Undrained bearing capacity of the cutting face for an open caisson - Royston, R; Sheil, B; Byrne, B (ICE Publishing, 2021)
Large-diameter open caissons are an increasingly common means of constructing underground storage and attenuation tanks, as well as launch and reception shafts for tunnel-boring machines. A ‘cutting face’ at the base of the caisson wall, resembling an inclined ring footing, is typically used to aid the sinking phase. This paper describes a suite of over 15 000 finite-element limit analyses exploring the bearing capacity of a caisson cutting face, partially or wholly embedded in undrained soil. The primary aim of the study is to assess the influence of the cutting face inclination angle on the vertical bearing capacity. The effects of cutting face roughness, internal overburden and surcharge, and caisson radius are also investigated. In particular, the results indicate that a steepening of the inclination angle may not always reduce the bearing capacity, if the cutting face is rough. The numerical output informs the development of a closed-form approach for application in routine design. The new design method is shown to provide an excellent representation of the numerical output.